Experimental Study and Microscopic Analysis on Frost Resistance of Iron Ore Tailings Recycled Aggregate Concrete - Li Gong; Xuelei Gong; Ying Liang; Zhiyuan Jia; Yiqiang Li (Advances in Materials Science and Engineering)
Freeze-thaw harm is the major factor that reduces the durability of hydraulic concrete buildings at high altitudes and in cold regions. To solve the durability problem of hydraulic buildings in alpine regions, the study prepared sixteen groups of concrete specimens with different replacement ratios of iron ore tailings and recycled aggregate were prepared, and indoor deterioration accelerated tests were designed. Nuclear magnetic resonance (NMR) technology was used to analyze the pore distribution in the structure, and macro indicators of concrete mass loss rate and relative dynamic elastic modulus (RDEM), were selected. Combined with SEM, images, the frost resistance of iron ore tailings sand (IOT), with Recycled aggregate concrete (RAC), was explored. The final analysis shows that when only RCA is replaced, the frost resistance of RAC decreases with the increase of the RCA replacement rate. When only replacing IOT, the frost resistance of IOT concrete with a replacement rate of 50% is better than that of other replacement rates. In addition to ordinary concrete, the combination of 30% iron ore tailings and 30% recycled aggregate concrete (RAC3-IOT3) has good frost resistance. The mass loss of the RAC3-IOT3, specimen increased by 0.09% compared with ordinary concrete. From the microscopic level, with the addition of the dosage of RCA, the number of macropores (0.05∼1 μm) and microcracks (>1 μm) in concrete increased. After replacing the appropriate amount of iron ore tailings, the pore space structure of RAC was improved, and some harmful pores spaces were transformed into harmless pores. However, the combination of excess IOT, and RCA, does not improve the interface transition zone of RCA. From the micromorphology, with an increasing dosage of RCA, the bonding force between cementitious material and sand aggregate weakens and there are more pores. The combination of excess IOT, and RCA, does not improve the interface transition zone of RCA but will accelerate the spalling of surface mortar because of its small fineness. All things considered, RAC3-IOT3 is the most suitable concrete for high altitude and cold areas.